PORTUGUÊS COMO LÍNGUA DE ACOLHIMENTO PARA ACESSO A DIREITOS HUMANOS: POLÍTICAS LINGUÍSTICAS E REFLEXÕES A PARTIR DA ANÁLISE DE MATERIAIS DIDÁTICOS PARA MIGRANTES - Priscila de Pinho Valente (Nepan editor, 2019)
Faced with the migration of Senegalese people to the city of Rio Grande, RS and the linguistic difficulties that stand out as their survival needs, it is noticed a lack of a language policy of social impact aimed at this group. In this article, we discuss methodological proposals for the teaching of Portuguese as a hosting language (GROSSO, 2010) for migrants and refugees based on the language policies adopted in Brazil. According to Action-Oriented Approach on Language Teaching (JANOWSKA, 2014; PUREN, 2009), Task-based Approach (ELLIS, 2000; JA-NOWSKA, 2014, SHIBAYAMA, 2017, WILLIS, 2012) and the analysis of some specific didactic materials for immigrants, it will be presented a proposal of foreign language teaching that goes beyond the linguistic training, aiming at the development of discursive competences and promoting reflection on the relation of language with the guarantee of the human rights for the full integration of migrants into society.